The Little, Brown handbook - Fowler, H. Ramsey (HarperCollins, 1992)
Includes bibliographical references and index; 9 parts: The whole paper and paragraphs; grammatical sentences; clear sentences; effective sentences; punctuation; mechanics; effective words; research writing; practical writing.